Interbrain phase synchronization during turn‐taking verbal interaction—a hyperscanning study using simultaneous EEG/MEG - Ahn, Sangtae; Cho, Hohyun; Kwon, Moonyoung; Kim, Kiwoong; Kwon, Hyukchan; Kim, Bong Soo; Chang, Won Seok; Chang, Jin Woo; Jun, Sung Chan (Human brain mapping, 2018)
Recently, neurophysiological findings about social interaction have been investigated widely, and hardware has been developed that can measure multiple subjects' brain activities simultaneously. These hyperscanning studies have enabled us to discover new and important evidences of interbrain interactions. Yet, very little is known about verbal interaction without any visual input. Therefore, we conducted a new hyperscanning study based on verbal, interbrain turn‐taking interaction using simultaneous EEG/MEG, which measures rapidly changing brain activities. To establish turn‐taking verbal interactions between a pair of subjects, we set up two EEG/MEG systems (19 and 146 channels of EEG and MEG, respectively) located ∼100 miles apart. Subjects engaged in verbal communication via condenser microphones and magnetic‐compatible earphones, and a network time protocol synchronized the two systems. Ten subjects participated in this experiment and performed verbal interaction and noninteraction tasks separately. We found significant oscillations in EEG alpha and MEG alpha/gamma bands in several brain regions for all subjects. Furthermore, we estimated phase synchronization between two brains using the weighted phase lag index and found statistically significant synchronization in EEG and MEG data. Our novel paradigm and neurophysiological findings may foster a basic understanding of the functional mechanisms involved in human social interactions. Hum Brain Mapp 39:171–188, 2018. © 2017 Wiley Periodicals, Inc.